A Transdiagnostic Perspective on Unwanted Intrusive Thoughts in Eating Disorders and Obsessive-Compulsive Disorder and Their Relationship with Early Maladaptive Schemas: A Path Modeling Analysis - Uluyol, Fatma Mahperi (The European Research Journal, 2026)
Objectives: Unwanted intrusive thoughts (UITs) are sudden, repetitive, ego-dystonic cognitions commonly observed across psychological disorders, including obsessive-compulsive disorder (OCD) and eating disorders (EDs). Despite disorder-specific content, their shared features - such as intrusiveness and suppression urges - suggest a transdiagnostic cognitive function. Early maladaptive schemas (EMSs), as deep cognitive structures, may shape how individuals interpret and respond to UITs, thereby influencing symptom severity. While some EMSs broadly relate to psychopathology, others appear disorder-specific. However, studies jointly examining UITs and EMSs across OCD and EDs within the same sample remain scarce. This study aims to explore the transdiagnostic and disorder-specific roles of UITs and EMSs in relation to OCD and ED symptoms by analyzing their shared and distinct associations in a non-clinical sample. Methods: A total of 364 university students (270 females, 94 males) completed self-report measures assessing UITs related to EDs and OCD, EMSs, and ED/OCD symptomatology. Path analysis was conducted in Analysis of Moment Structures (AMOS) to test the theoretical model. Results: EMS domains were differentially associated with UITs and symptom severity in OCD and EDs. Other-Directedness predicted OBQ (β=0.32) and indirectly OCI-R (β=0.06). Impaired Autonomy was linked to both OBQ (β=0.23) and EDITs (β=0.48), while Impaired Limits was associated only with OCI-R (β=0.18). OBQ predicted OCI-R (β=0.20) and EDITs predicted both EDE-Q (β=0.65) and OBQ (β=0.17). Conclusions: UITs and specific schema domains may jointly contribute to EDs and OCD symptoms, suggesting targets for early intervention in subclinical populations.